(untitled) (Academicia Globe: Inderscience Research, 2025)
This study is dedicated to a scientific analysis of the regional characteristics of the formation and development of the human capital market in the Khorezm region, as well as an assessment of its impact on economic growth. The research analyzes the structure of labor resources, the ratio of economically active and inactive population, and employment and unemployment levels across districts using statistical and economic analysis methods. The findings indicate that although the Khorezm region possesses sufficient quantitative human capital potential, its qualitative integration into economic activity remains limited. The declining share of the working-age population, territorial disparities in employment, and low economic participation of youth and women highlight the need to improve human capital market development mechanisms. The study proposes a multidimensional economic model illustrating the interconnections between human capital, investments, innovations, and production efficiency in driving economic growth. Based on the results, scientific and practical recommendations are formulated to promote territorially differentiated development of the human capital market, strengthen the alignment between education and labor markets, and modernize the healthcare system from a human capital development perspective.